Caribbean Report 04-03-1997 - Richards, Ken (anchor); Allen, Don (interviewee); Patterson, P. J. (interviewee); Bird, Lester (interviewee); Maraj, Ralph (interviewee); Niles, Bertram (anchor); Gordon, Warren (correspondent); Ismael, Odeen (interviewee); Thomas, Moya (correspondent) (The British Broadcasting Corporation, 1997)
Jamaica’s Chamber of Commerce says that it has serious problems with the crime situation and is willing to contribute to the efforts to reduce violence on the island. Next, the Prime Minister of Jamaica, P.J. Patterson has called for a regional agreement with the United Sated to fight gun smuggling in Jamaica. Next, Trinidad and Tobago Foreign Minister says bilateral talks being held with the United States envoy is just a prelude to a meeting between the US official and the Community of Caricom Ministers. In this segment, there is hope that the Caribbean will see a decrease in the drug trafficking problem. The hope is based on the impending implementation of a regional anti-narcotic action plan with significant backing from the European Union and the United States. Next, synthetic drugs are becoming a major problem because of the increase in trade and consumption, according to a warning by the International Narcotics Control Board. Next, according to reports coming out of Guyana’s Washington Embassy, President Jagan remains in an extremely critical condition. Finally, Due to their economic embargo against Cuba, the United States is being accused of being responsible for the alleged deplorable conditions in Cuban hospitals. However, they are dismissing such allegations.
1. Headlines (00:00-00:28)
2. Jamaica's Chamber of Commerce says it has serious problems with the crime situation on the island and intends contributing to the efforts to reduce violence. Don Allen, Jamaica's Chamber of Commerce Executive Director is interviewed (00:29-03:57)
3. Prime Minister of Jamaica, P.J. Patterson has called for a regional agreement with the United States to fight gun smuggling. P.J. Patterson is interviewed (03:58-05:42)
4. Trinidad and Tobago's Foreign Minister, Ralph Maraj speaks out on the bilateral talks with United States Envoy, Richard Clarke. Ralph Maraj, Trinidad and Tobago's Foreign Minister and Lester Bird, Caricom Chairman are interviewed (05:43-07:27)
Keywords: Chamber of Commerce -- Jamaica.; Crime -- Jamaica.; Gun smuggling -- Jamaica.; Clarke, Richard.; Community of Caricom Ministers.; Bilateral talks -- Caribbean region.; Drug trafficking -- Caribbean.; Anti-narcotic Action Plan.; International Drugs Congrol Programme -- Caribbean Office.; Drugs -- Synthetic.; Jagan, Cheddi.; Guyana's Washington Embassy.; Deplorable hospital conditions -- Cuba.; United States Embargo -- Cuba.